Differences in Salivary Calcium Levels and Oral Hygiene Status in Elderly Men and Women in Suka Maju Village, Deli Serdang Regency - Pitu Wulandari; Irma Ervina; Armia Syahputra; Syafira Yan; Julia Maharani (Jurnal Penelitian Pendidikan IPA, 2026)
Previous studies have examined salivary calcium and periodontal disease; however, evidence regarding sex-related differences in salivary calcium levels and oral hygiene status among elderly individuals with periodontitis, particularly in Indonesia, remains limited. This gap highlights the need for studies that can support more targeted oral health assessment and management in geriatric dentistry. This study aimed to analyze differences in salivary calcium levels and oral hygiene status between elderly men and women in Suka Maju Village, Deli Serdang Regency. This observational analytic study used a cross-sectional design. The subjects consisted of 88 elderly individuals. Oral hygiene was assessed using the calculus index, debris index, and Oral Hygiene Index (OHI), while salivary calcium levels were analyzed using spectrophotometry. The results showed that salivary calcium levels were higher in elderly men than in women. Most subjects in both groups had poor oral hygiene status. There was a significant difference in salivary calcium levels between elderly men and women (p = 0.004), while no significant difference was found in oral hygiene status between the two groups (p = 0.950). As the conclusion in elderly individuals with periodontitis, salivary calcium levels differ between females and males, with females having higher levels than males. The male OHI is higher than the female OHI, but there is no significant difference between the two.